2001
DOI: 10.3310/hta5130
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of temozolomide for the treatment of recurrent malignant glioma: a rapid and systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Eight full reports of six studies were identified for inclusion in the main review (Dinnes et al, 2001). Only the five studies providing effectiveness data for temozolomide in patients with AA or GBM are reported here (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight full reports of six studies were identified for inclusion in the main review (Dinnes et al, 2001). Only the five studies providing effectiveness data for temozolomide in patients with AA or GBM are reported here (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…More detailed discussion of factors that affect various outcome measures and how the included studies addressed these factors can be found in the full report (Dinnes et al, 2001). …”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic Cochrane type review of published articles (described in detail in the full publication (Dinnes et al, 2001) concludes that the evidence base for the use of Temozolomide in malignant glioma is 'weak and few strong conclusions can be drawn regarding its effectiveness' (Dinnes et al, this issue). This is in stark contrast to the description of the agent during its launch as 'the most important advance in brain cancer treatment for the past 20 years'.…”
mentioning
confidence: 99%